2006
DOI: 10.1073/pnas.0602816103
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of proteins based on characteristic patterns of association and denaturation in solutions of SDS

Abstract: This paper shows that proteins display an unexpectedly wide range of behaviors in buffers containing moderate (0.1-10 mM) concentrations of SDS (complete unfolding, formation of stable intermediate states, specific association with SDS, and various kinetic phenomena); capillary electrophoresis provides a convenient method of examining these behaviors. Examination of the dynamics of the response of proteins to SDS offers a way to differentiate and characterize proteins. Based on a survey of 18 different protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 24 publications
2
84
1
1
Order By: Relevance
“…Unboiled SVD exhibited two broad faster peaks (7 and 9 min) that suggest the presence of multiple SVD species with different sensitivity to SDS. The existence of more than one type of protein:SDS species was also found by Gudiksen K. L. et al, 9 who observed a mixture of protein:SDS complexes with similar migration times that resulted in broadening of the peak. They suggested that the various peaks result from the different number of SDS molecules binding to various protein conformations.…”
Section: Resultssupporting
confidence: 72%
“…Unboiled SVD exhibited two broad faster peaks (7 and 9 min) that suggest the presence of multiple SVD species with different sensitivity to SDS. The existence of more than one type of protein:SDS species was also found by Gudiksen K. L. et al, 9 who observed a mixture of protein:SDS complexes with similar migration times that resulted in broadening of the peak. They suggested that the various peaks result from the different number of SDS molecules binding to various protein conformations.…”
Section: Resultssupporting
confidence: 72%
“…Interactions of CA with detergents have not been studied extensively, although in recent studies, Whitesides and co-workers 652,657,706,760,761 Early studies of proteins denatured with SDS suggested that two distinct conformations exist in solutions containing low (0.025%) and high (0.1%) (w/v) concentrations of SDS (referred to as the low-and high-binding states, respectively), 762,763 and that both are enzymatically inactive. 757 CD studies indicated that both the high-and low-binding states have conformations that are different from either the native enzyme or the denatured state with GuHCl.…”
Section: Sodium Dodecyl Sulfate (Sds)mentioning
confidence: 99%
“…For a number of proteins, the CE patterns showed [10] a sudden shift of the sample peaks at a given SDS concentration (which was not the CMC). Furthermore, the peak shape changed and in some cases multiple peaks were observed.…”
Section: Introductionmentioning
confidence: 95%